Pengaruh Inflasi, Nilai Tukar Rupiah pada Dollar Dan Tingkat Suku Bunga terhadap Permintaan Kredit Pada Perusahaan Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2016 - Marlina Marlina (JURNAL PROINTEGRITA, 2019)
Credit is one part of capital formation carried out by financial institutions in this case the banking sector to the society in an effort to encourage business performance so that it can be used to increase the productivity of real sector businesses carried out by the community individually or in groups. Credit demand can be influenced by several factors including inflation, exchange rates and interest rates. The theory used in this study is a theory relating to corporate finance, inflation, exchange rates, interest rates and credit demand. This research is a quantitative descriptive approach. Data collection techniques used are documentation techniques and secondary data collection from financial statements of Banking Sector companies that are listed on the Indonesia Stock Exchange for the period 2013-2016. The population in this study is 43 Banking Sector companies listed on the Indonesia Stock Exchange for the period 2013-2016, while the total number of samples used in this study is 23 companies with 4 research periods with a total of 92 observations. The analysis model in this study is multiple linear regressions using the SPSS program. Data testing was done by classical assumption test, test coefficient of determination, F test and t test. The conclusions from the results of this study are partially and simultaneously inflation, exchange rates and interest rates have no significant effect on the demand for credit in the Banking Sector Companies Listed on the Indonesia Stock Exchange Period 2013-2016. The value of the hypothesis determination coefficient is 0.006 which means 0.6% Variable variation. Request credit (Y) can be explained by variations in the variables of inflation, exchange rates and interest rates